2022
DOI: 10.1039/d1sm01763b
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput microscopy to determine morphology, microrheology, and phase boundaries applied to phase separating coacervates

Abstract: Evolution of composition, rheology, and morphology during phase separation in complex fluids is highly coupled to rheological and mass transport processes within the emerging phases, and understanding this coupling is...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 52 publications
1
19
0
Order By: Relevance
“…This reduces the excluded volume asymmetry between the two phases, and, as a result, the salt partitioning ratio increases from values less than 1 toward 1. Although experimental efforts have shown that the salt partitioning behavior is not universal and depends on other factors such as the chemistry of the PE and charge density, , our prediction of higher salt partitioning in the dilute phase is consistent with the experimental observations for the stoichiometric PAA/PAH mixture. , …”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…This reduces the excluded volume asymmetry between the two phases, and, as a result, the salt partitioning ratio increases from values less than 1 toward 1. Although experimental efforts have shown that the salt partitioning behavior is not universal and depends on other factors such as the chemistry of the PE and charge density, , our prediction of higher salt partitioning in the dilute phase is consistent with the experimental observations for the stoichiometric PAA/PAH mixture. , …”
Section: Resultssupporting
confidence: 87%
“…The phase diagram from the Gaussian approximation for N = 150 at 1:1 stoichiometry is directly compared to experimental results of the similar system reported by Li et al and Luo et al at pH = 6.5 (Figure ). , While qualitatively capturing the screening effect of added salt, the phase diagram shown here (1) overestimates the critical salt concentration and (2) underestimates the PE compositions in the coacervate phase. Deficiency (1) is largely attributable to the Gaussian approximation which neglects higher-order fluctuations that become more important near the critical point (can be resolved by including fields other than the electrostatic potential).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Low solution turbidity in this regime is consistent with the small fraction of droplets observed via optical microscopy. It is possible that differences in salt partitioning between polypeptide complexes and bulk solvent that is known to occur in coacervating systems may result in phase instability under these conditions. It is important to note here that MD simulations were unable to delineate the nanostructure of the polypeptide complexes in region V due to the absence of force fields able to reproduce such high solubility of sodium chloride salt.…”
Section: Discussionmentioning
confidence: 99%